Occurrence and distribution of the environmental pollutant antibiotics in Gaoqiao mangrove area, China. (March 2016) - Li, Yuan; Li, Qin; Zhou, Kai; Sun, Xing-Li; Zhao, Li-Rong; Zhang, Yu-Bin
Abstract: Occurrence and distribution of 15 antibiotics belonging to families of sulfonamides, fluoroquinolones, tetracyclines and chloramphenicols were investigated in water and sediment in Gaoqiao mangrove area, China, using LC-MS-MS. The influence of tidal level and mangrove vegetation on antibiotic residues were examined. The levels of antibiotics were found to be ranged from 0.15 to 198 ng L −1 in water and from 0.08 to 849 μg kg −1 in sediment. No significant difference in concentrations of 15 different antibiotics from water and sediment samples was observed among the high, middle and low intertidal channel. The residues of SMZ, SMTZ, OFL, NOR, ENR, OXY and FLO were significantly higher in Aegiceras corniculatum assemblage than in Avicennia marina assemblage. Although no significant difference in tested antibiotics was found between the surface and bottom sediment, mangrove vegetation can to some extent reduce the accumulation for SMZ, SMTZ, OFL, NOR, CIP, OXY and TET in sediments relative to corresponding bare mudflats, implying that the environmental pollution from antibiotics may be mitigated by mangrove vegetation. Principal components analysis revealed that the terrestrial input and different habitats directly influenced the occurrence and distribution of antibiotics. Highlights: Antibiotics used in aquaculture were commonly occurred in mangroves. Antibiotic residues and pollutions are relevant to different antibiotic families, influenced by tidal level in mangroves. Antibiotic pollutions can be mitigated with mangrove vegetation to some extent.